Beyond the pandemic? : exploring the impact of covid-19 on telecommunications and the internet - Whalley, Jason; Stocker, Volker; Lehr, William (Emerald Publishing Limited, 2023)
This book contains an Open Access chapter The COVID-19 pandemic disrupted economies and society globally. In addressing the crisis, the Internet proved incredibly important in enabling many to shift physical work, education, and social activities online and facilitating the tracking of the progress of the pandemic. Beyond the Pandemic? is the first edited collection to concentrate on the dynamic and complex relationship between the Internet and the role it played in responding to the pandemic. Covid-19 accelerated the digital economy transformation, changing the way work, education, and social engagement is organized, potentially permanently. The collection of international scholars who contributed to this volume offer insightful perspectives on how the Internet ecosystem responded and was changed as a consequence of Covid-19; the sectoral consequences of shifting activity online that the Internet enabled for many, but not for all; and the implications for regulatory policies. Given how central digital technologies are to all aspects of business, society, and government, Beyond the Pandemic? is integral to the exploration of the sectoral consequences of the Internet for business managers, policymakers and researchers engaged in planning and study for the digital economy future and planning for future pandemics.